Nanosuspensions of Selexipag: Formulation, Characterization, and in vitro Evaluation - Rusul M. Alwan; Nawal A. Rajab (College of Pharmacy University of Baghdad, 2021)
Selexipag is an orally selective long-acting prostacyclin receptor agonist, which indicated for the treatment of pulmonary arterial hypertension. It is practically insoluble in water ( class II, according to BCS). This work aims to prepare and optimized Selexipag nanosuspensions to achieve an enhancement in the in vitro dissolution rate. The solvent antisolvent precipitation method was used for the production of nanosuspension, and the effect of formulation parameters (stabilizer type, drug: stabilizer ratio, and use of co-stabilizer) and process parameter (stirring speed) on the particle size and polydispersity index were studied. SLPNS prepared with Soluplus® as amain stabilizer (F15) showed the smallest particle size 47nm with PDI and Zeta potential value of 0.073 and -47mV, respectively. SLPNS exhibited an increase in the dissolution rate in phosphate buffer pH 6.8 (100% drug release during 60 min) compared to the pure drug ( 40% during the same time). This result indicates that SLPNS is an efficient way of improving the dissolution rate.